An Analysis of the Implementation of Formative Evaluation as an Effort to Improve Students’ Academic Achievement - Tambak, Aminah; Setiawan, Hasrian Rudi; Nurdianti, Nurdianti; Lestari, Sri Putri; Intan, Nur (Kitabah: Jurnal Pendidikan Sosial Humaniora, 2025)
This study aims to analyze the implementation of formative evaluation in improving students’ academic achievement. Formative evaluation is a type of continuous assessment conducted during the learning process to monitor students’ progress, provide feedback, and improve teaching strategies. The research method employed is a qualitative approach using literature study and descriptive analysis techniques. The findings indicate that the application of formative evaluation enhances learning motivation, improves conceptual understanding, and positively impacts students’ academic achievement. Therefore, formative evaluation is highly effective in improving learning outcomes when applied systematically and consistently.